Religiosity and Self-Efficacy in the Prevention of HIV-Risk Behaviours among Muslim University Students - Angga Wilandika (Universitas Airlangga, 2018)
Introduction: The high prevalence of HIV infection among an age group of 18–25 years, both globally or nationally, was indicating students vulnerable to HIV/AIDS infections. Prevention of HIV risk behaviours can be used as a religiosity approach to strengthening the self-efficacy on prevention HIV-risk behaviour. However, there were limited studies on the association between religiosity and self-efficacy on prevention of HIV-risk behaviour among student, especially Muslim students. The aims of this study were to identify the correlation between religiosity with self-efficacy in the prevention of HIV-risk behaviours.Methods: The study employed a correlation study. The sample size comprised 404 Muslim university students with proportionate stratified random sampling. Student’s religiosity was measured by The Muslim Piety questionnaire and self-efficacy was measured by Self-Efficacy in the Prevention of HIV-Risk Behaviour questionnaire. Descriptive analysis using mean, standard deviation, percentage and frequency distribution. Meanwhile, inferential analysis using Pearson's Correlation.Results: The results were found that most of the students have high levels of religiosity and strong self-efficacy in the prevention of high-risk behaviour. Further analysis revealed a significant (p < 0.005) and strong correlations (r = 0.6780) between religiosity and self-efficacy in the prevention of HIV-risk behaviour. Higher levels of religiosity were followed by higher levels of self-efficacy on the prevention of HIV-risk behaviours among students.Conclusion: findings can be used by academic and health professionals, to implement a religiosity based program to strengthen a self-efficacy of HIV-risk behaviour. Further research can be a focus on the nursing interventions based on religious beliefs to strengthen self-efficacy in the prevention of HIV/AIDS infections.